Evaluasi Pelaksanaan Tes Tertulis di TKIT. Nurussyifa dalam Implementasi Kurikulum Merdeka - Febrianti, Deriana; Rahayu, Mustika Qoiriyah; Mustikasari, Riski (STKIP PGRI Ponorogo Press, 2024)
Early childhood is the nation's next generation whose development and growth we must maximize. During this golden age, children receive stimulation from the environment at home, at school and in the community. At school, teachers provide stimulation to children through learning activities according to the kurikulum merdeka. In the pre-school period, children are also introduced to basic writing activities. Indicators of beginning writing are, the child can hold a writing instrument well and correctly, is able to move his hand well, the child can imitate letter shapes, the child can recognize letter shapes. Writing test activities in kindergarten are implemented with very simple activities such as bolding letters, making dashes, making shapes and many more. This research was conducted to evaluate written test activities at TKIT Nurussyifa Krebet Jambon Ponorogo. The data sources in this research are the principal, group A teachers, and group A1 students at TKIT Nurussyifa. The method used in this research is a qualitative research method, using a field case study approach. The techniques used in collecting data are observation, interviews and documentation. From the research results, the written test activities carried out at TKIT Nurussyifa have gone well, and are not burdensome for therapy children, showing positive results and are effective in training children's motor skills in beginning writing.